Poíticas públicas municipais de economia solidária e a dimensão sociopolítica dos empreendimentos econômicos solidários - Vanderson Gonçalves Carneiro (2012)
The research analyzes data to different recognitions solidarity economy, based on a bias of inequality and / or the difference, being that these recognitions guide practices and public actions promoted for its development. In this sense, the different types of recognitions and policies are seen as current of social constructions us which different subject with different political projects. Therefore, the research draws attention that as important as the analysis of policies that are dedicated to explain the inclusion of solidarity economy on the policy agenda, as well as the analyzes on their evaluations, are the analyzes of the type of understanding and recognition given the solidarity economy and its actors, and consequently their policies. For this, it analyzes twenty two laws that they institutionalise Municipal policy of solidarity economy and demand classifies them, from three dimensions, in two types of policies that synthesize different perspectives and interpretations of what is, and what may represent the development of actions of solidarity economy. The differences in policies are related to three contexts of the municipalities that created the laws, namely, the socioeconomic context, the political institutional context and practices, and actors. From contingency tables trying to see associations between context variables with the types of policies and seeks to answer the hypothesis that a socio-political dimension of solidarity economic enterprises (related to the context of practices and actors) highlights the role of actors in the recognition solidarity economy under a bias of difference, and as this type of recognition and influence on performance has a type of policy of solidarity economy more sustainable and inclusive as opposed to a type of policy of solidarity economy more utilitarian-insertional-competitive.